PEMBERDAYAAN MASYARAKAT DESA CANDI MELALUI PENGEMBANGAN USAHA PEMBENIHAN DAN BUDIDAYA LELE DI ERA COVID-19 - Mustofa, Sheila; Nurfathurrohman, Muhammad (Perkumpulan Pendidikan Islam Anak Usia Dini Wilayah Sumatera, 2021)
The Covid-19 pandemic has greatly affected human life. One of the efforts to empower communities affected by Covid-19 in Candi Village, Ampel District, Boyolali Regency, is by optimizing the village's potential, namely abundant water sources. The aim of carrying out this community service activity is to help people create new income and skills so that they can be independent, develop, and not always depend on government assistance. This is done through a new method, namely the catfish cultivation business in Candi Village. People need to know how important it is to remain entrepreneurial during this pandemic. This community service activity takes the form of outreach, education and direct training regarding catfish cultivation. The hope of this service is that it can help the residents of Candi Village in terms of income and entrepreneurship in the midst of the Covid-19 Pandemic.